Financial provision of the social policy - Serkebayeva, R.K.; Kazbekov, G.K.; Samatova, L.A. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
Social policy, in a narrow sense, presupposes social relations in which a state undertakes to maintain stability in the society, ensure a decent standard of living for a part of the population that due to age or life situations needs special public support and care. In a broad sense, social policy expresses the state's ability to provide opportunities for personal growth and a decent life for its’ citizens, including the development of the social infrastructure — education, health care, culture, all of which determine the level and quality of life in the society. In the conduct of social policy Kazakhstan adheres to the world practice. The goal of social policy has always been providing decent quality and standard of living for the population In the population income policy the state follows the two basic approaches: a) it creates favorable conditions for able-bodied citizens to receive and earn decent incomes; b) it provides social protection and support for the disabled and those categories of the population who for objective reasons are not able to achieve a minimum acceptable standard of living. During the adaptation of the Republican budget for the corresponding financial year, the sizes of social pensions, the minimum wage, and the monthly calculated index are annually reviewed.
Əлеуметтік саясаттың қаржылық қамтамасыздандырылуы
Финансовое обеспечение социальной политики
Keywords: man; social policy; income; finance; standard of living; quality of life; entrepreneurship; consumer basket